2022
DOI: 10.3390/economies10040088
|View full text |Cite
|
Sign up to set email alerts
|

Maritime Policy Design Framework with ESG Performance Approach: Case of Estonia

Abstract: In policy-making, the design of a policy is considered to be one of the most significant steps. A well designed policy will be able to solve sectoral problems across stakeholders as well as support the competitive development of the entire economy. Enterprises of the maritime sector have been influenced by environmental, social, and governance (ESG) changes with the push coming from financiers, insurers, regulators, and customers. To meet the ESG challenges and utilize the benefits ahead, they need to be addre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 28 publications
0
20
0
Order By: Relevance
“…The literature review showed that most of the research is focused on sustainable development actions in the private sector and few studies pay attention to policy-making in the maritime sector regarding sustainability matters [6,7]. Nõmmela and Kõrbe Kaare [9] studied how to design a maritime policy with the ESG approach and proposed a framework for policy design that is the first step of the policy-making cycle. They also exemplified the evaluation of policy compliance to the ESG criteria using the ESG indicators proposed in the same research [9] and proposed an index for the maritime cluster impact assessment as input for policy-making.…”
Section: Incorporating Sustainability Into Strategiesmentioning
confidence: 99%
See 4 more Smart Citations
“…The literature review showed that most of the research is focused on sustainable development actions in the private sector and few studies pay attention to policy-making in the maritime sector regarding sustainability matters [6,7]. Nõmmela and Kõrbe Kaare [9] studied how to design a maritime policy with the ESG approach and proposed a framework for policy design that is the first step of the policy-making cycle. They also exemplified the evaluation of policy compliance to the ESG criteria using the ESG indicators proposed in the same research [9] and proposed an index for the maritime cluster impact assessment as input for policy-making.…”
Section: Incorporating Sustainability Into Strategiesmentioning
confidence: 99%
“…Nõmmela and Kõrbe Kaare [9] studied how to design a maritime policy with the ESG approach and proposed a framework for policy design that is the first step of the policy-making cycle. They also exemplified the evaluation of policy compliance to the ESG criteria using the ESG indicators proposed in the same research [9] and proposed an index for the maritime cluster impact assessment as input for policy-making. This index included three indicators: Economic impact, sociocultural impact, and environmental impact [31].…”
Section: Incorporating Sustainability Into Strategiesmentioning
confidence: 99%
See 3 more Smart Citations